Plant communities and alien invasion in Kalika community forest, Kailai district, Sudurpashchim Province, Nepal - Sapkota, Jeewan; Pant, Ramesh Raj; Pokhrel, Chandra Prasad; Thapa, Lal B. (Geographical Journal of Nepal, 2023)
One of the major threats to native biological diversity is caused by invasive alien plant species (IAPS). As the documentation of plant communities and alien plant invasion in Far-west Nepal is very scarce, this study was carried out in the Kalika community forest of Kailali district, Sudurpaschim Province, Nepal. The aim of the study was to identify plant communities and the status of IAPS in the forest. A total of 43 plots (size 10 m × 10 m) were sampled. Plant communities were distinguished based on the Sorenson similarity index and cluster dendrogram. Cover of the tree canopy and IAPS was measured. A total of 101 species of vascular plants were recorded from five types of plant communities in the forest. The communities were named as (i) Buchanania latifolia-Terminalia alata community (ii) Casearia glomerata-Mallotus philippensis community (iii) Shorea robusta-Terminalia alata community (iv) Adina cordifolia-Mallotus philippensis community (v) Terminalia-Shorea-Trewia mixed community. These communities were invaded by invasive Ageratum houstonianum, A. conyzoides, Bidens pilosa, Cassia tora, and Argemone mexicana. A high cover of IAPS was found in Terminalia-Shorea-Trewia mixed community. The cover of IAPS was low under the high tree canopy. Control and management of IAPS should be done to protect the native plant communities in the forest for reducing disturbance to maintain tree canopies. It is hoped to be an effective method to reduce alien plant invasions.